CCL4‐mediated targeting of spleen tyrosine kinase (Syk) inhibitor using nanoparticles alleviates inflammatory bowel disease. Issue 2 (17th February 2021) - Gong, Wenbin; Yu, Jiafei; Zheng, Tao; Liu, Peizhao; Zhao, Fan; Liu, Juanhan; Hong, Zhiwu; Ren, Huajian; Gu, Guosheng; Wang, Gefei; Wu, Xiuwen; Zhao, Yun; et al.
Abstract: Inflammatory bowel disease (IBD) has emerged a global disease and the ascending incidence and prevalence is accompanied by elevated morbidity, mortality, and substantial healthcare system costs. However, the current typical one‐size‐fits‐all therapeutic approach is suboptimal for a substantial proportion of patients due to the variability in the course of IBD and a considerable number of patients do not have positive response to the clinically approved drugs, so there is still a great, unmet demand for novel alternative therapeutic approaches. Spleen tyrosine kinase (Syk), a cytoplasmic nonreceptor protein tyrosine kinase, plays crucial roles in signal transduction and there are emerging data implicating that Syk participates in pathogenesis of several gut disorders, such as IBD. In this study, we observed the Syk expression in IBD patients and explored the effects of therapeutic Syk inhibition using small‐molecule Syk inhibitor piceatannol in bone marrow–derived macrophages (BMDMs). In addition, due to the poor bioavailability and pharmacokinetics of small‐molecule tyrosine kinase inhibitors and superiority of targeting nanoparticles‐based drug delivery system, we herein prepared piceatannol‐encapsulated poly(lactic‐co‐glycolic acid) nanoparticles that conjugated with chemokine C–C motif ligand 4 (P‐NPs‐C) and studied its therapeutic effects in vitro in BMDMs and in vivo in experimental colitis model. Our results indicated that in addition to alleviating colitis, oral administration of P‐NPs‐C promoted the restoration of intestinal barrier function and improved intestinal microflora dysbiosis, which represents a promising treatment for IBD. Abstract : 1. The expression level of Syk increased in inflamed colon mucosa tissues from IBD patients and was associated with disease activity. 2. Piceatannol‐encapsulated poly(lactic‐co‐glycolic acid) nanoparticles that conjugated with chemokine CCL4 (P‐NPs‐C) alleviates experimental colitis. 3. Oral administration of P‐NPs‐C promotes the restoration of intestinal barrier function and improves intestinal microflora dysbiosis.